Comparison of the inoculum size effects of antibiotics on IMP-6 β-lactamase-producing Enterobacteriaceae co-harboring plasmid-mediated quinolone resistance genes. - Yoshihiko Ogawa; Ryuichi Nakano; Kei Kasahara; Tomoki Mizuno; Nobuyasu Hirai; Akiyo Nakano; Yuki Suzuki; Naoki Kakuta; Takashi Masui; Hisakazu Yano; Keiichi Mikasa (PLoS ONE, 2019)
Almost all cases of carbapenemase-producing Enterobacteriaceae infections in Japan are caused by blaIMP-positive Enterobacteriaceae (especially blaIMP-6) and infections caused by other types of carbapenemase-producing Enterobacteriaceae are quite rare. We examined drug resistance genes co-harboring with blaIMP-6 and their inoculum size effects. We screened β-lactamase genes, plasmid-mediated quinolone resistance (PMQR) genes, and aminoglycoside-modifying enzyme genes by PCR and performed sequencing for 14 blaIMP-6-positive Enterobacteriaceae. Further, all PMQR-positive isolates were submitted to conjugation and inoculum effect evaluation. Our data showed that 13 of the 14 isolates harbored CTX-M-2 and one co-harbored CTX-M-2 and CTX-M-1 as extended-spectrum β-lactamases. All isolates carried one or more PMQRs; aac(6')-Ib-cr was the most prevalent (92.8%), and was followed by oqxA (64.3%), qnrS (50%), oqxAB (21.4%), and qnrB (14.3%). However, Klebsiella pneumoniae contains chromosomal OqxAB. Inoculum size effects were significant in all strains for meropenem, 13 strains for imipenem, 7 for levofloxacin, and 3 for amikacin. We observed that 11 of the experimental strains (100%), 8 strains (72.7%), and 1 strain showed inoculum size effects for meropenem, imipenem, and amikacin, respectively. However, four strains harbored qnr genes and two strains harbored qnr genes and QRDR mutations concurrently; no inoculum size effect was seen for levofloxacin. The blaIMP-6-positive Enterobacteriaceae that we studied was found to harbor at least one plasmid-mediated drug resistance gene. The inoculum size effect for carbapenems was thought to be mainly due to IMP-6-type metallo-β-lactamase; however qnrB and qnrS also had a minimal impact on the inoculum size effect for levofloxacin.